Effect of polymorphism on IL1A to cancer susceptibility: Evidence based on 34,016 subjects - Haoran Xia; Yiding Chen; Jialin Meng; Chaozhao Liang (Artificial Cells, Nanomedicine, and Biotechnology)
IL-1α is closely related to the development and metastasis of cancer, and its polymorphisms have been reported affecting the susceptibility of malignancy tumors, yet the conclusions are controversial. Present an overall meta-analysis was performed to reach more general findings. Relevant literature was searched from Google Scholar, Web of Science, PubMed, EMBASE, CNKI database and Wanfang database, and the association among polymorphism and cancer risk was appraised by counting ORs and 95% CIs of overall and stratification analysis. The date from 15,586 cases and 18,430 controls in 40 publications were enrolled. There is significantly upregulated risk leads by rs3783553 in all genetic models, while the same tendency was found in all cancer types. The results also suggest a high risk of cancer susceptibility in patients carried rs1800587 polymorphism, of which draw out form allelic and homozygote models in overall studies, especially for cervical cancer. However, there are no significant results in analysis of rs17561. In a word, IL1A SNPs play an essential role in upregulating cancer susceptibility, and current analysis provides detail date for further study in the future.